2010
DOI: 10.1136/hrt.2009.181644
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise in apparently asymptomatic patients with moderate or severe aortic stenosis: relationship between cardiac index and revealed symptoms

Abstract: Revealed symptoms on treadmill exercise in apparently asymptomatic aortic stenosis were associated with lower peak myocardial VO(2) and lower peak stroke index during exercise. The strongest resting predictor of revealed symptoms and of peak cardiac index was the blood BNP level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 34 publications
2
27
1
Order By: Relevance
“…This observation is in contrast with previous reports that used patients with similar degrees of aortic stenoses, but indicated that increases in cardiac output occurred only via increases in heart rate [15]. It agrees, however, with a more recent study that included 37 patients with asymptomatic aortic stenoses [5]. We found a trend toward more frequent abnormal trajectories in those who had values for Vmax greater than 5 m/s, suggesting that with such severe aortic stenosis a significant decrease in stroke volume at peak exercise may be more common.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…This observation is in contrast with previous reports that used patients with similar degrees of aortic stenoses, but indicated that increases in cardiac output occurred only via increases in heart rate [15]. It agrees, however, with a more recent study that included 37 patients with asymptomatic aortic stenoses [5]. We found a trend toward more frequent abnormal trajectories in those who had values for Vmax greater than 5 m/s, suggesting that with such severe aortic stenosis a significant decrease in stroke volume at peak exercise may be more common.…”
Section: Discussioncontrasting
confidence: 57%
“…These measurements often facilitate a more detailed assessment of the cause of a functional limitation [6]. Determining cardiac output during exercise via inert gas rebreathing (IGR) is promising in patients with heart failure or aortic stenoses [5,7]. Cardiac output and stroke volume, as assessed by either pVO 2 and pO 2 pulse or IGR during exercise, are of great pathophysiological importance in patients with aortic stenoses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of studies in AS, although patients with moderate to severe asymptomatic AS who are limited by symptoms on exercise testing do have lower peak VO 2 and cardiac index than those who are limited by fatigue (10). Resting echocardiographic measures of stenosis severity and ejection fraction do not predict exercise capacity, although LVH and diastolic dysfunction may be important (3,11).…”
mentioning
confidence: 98%
“…These results thus suggest that exercise stress echocardiography may provide prognostic information additional to that obtained by standard exercise testing and resting echocardiography 10. Symptoms on treadmill exercise testing in 38 apparently asymptomatic patients with at least moderate AS were associated with a lower peak myocardial VO 2 , a lower peak stroke index during exercise and BNP levels 11. Increased valvuloarterial impedance (Z(va)) (which is calculated by dividing the estimated LV systolic pressure (systolic arterial pressure + mean transvalvular gradient) by the stroke volume indexed for the body surface area) is a marker of excessive LV haemodynamic load, and a value >3.5 successfully identifies patients with AS with a poor outcome 12.…”
Section: Aortic Stenosismentioning
confidence: 78%